Analysis of heart rhythm variability by linear and non-linear dynamics methods - Vuksanović Vesna; Gal Vera (Vojnosanitetski Pregled)
Introduction. Spectral analysis of heart rhythm variability is a noninvasive method to study cardiovascular autonomic control. Nonlinear methods of analysis of heart rhythm variability may provide an additional information on properties of RR interval dynamics, which cannot be revealed by linear methods. The aim of this study was to investigate and to compare some parameters of deterministic chaos, tractal and spectral properties of heart rhythm variability in healthy subjects. Methods. Sixty healthy subjects, who participated in this study, were divided in four different age groups: children (< 15 years old), young (15-24 years), adults (25-39 years) and middle-aged (40-61 years). We analyzed the heart period variability extracted from a 5-minute electrocardiograms recordings in supine rest. Short-term fractal scaling exponent, sample entropy, minimum embedding dimension and the largest Lyapunov exponent along with the spectral measures (low-frequency and high-frequency power) were determined. Results. Heart frequency, short-term fractal scaling exponent, and the largest Lyapunov exponent did not differ between the tested groups (p > 0.05). Middle-aged subjects had the lower low-frequency power as compared to the children (p < 0.001) and the young (p < 0.05), and the lower high frequency power as compared to the other three groups (p < 0.001). Middle-aged also had a significantly lower power of high frequency and sample entropy as compared to the other three groups (p < 0.001). Children had lower values of minimum embedding dimension compared to the middle aged (p<0.001). Significant negative correlation between the age of the tested subjects, and the low-and, high-frequency power and sample entropy was found. Conclusion. The obtained results suggested that healthy aging was associated with significant alteration in heart rhythm dynamics reflected on a higher regularity and lower variability of heart rhythm time-series. Significant decrease in a high-frequency power with aging suggested that reduction in parasympathetic activity was the basic cause of these changes.